2012
DOI: 10.1007/s11357-012-9457-z
|View full text |Cite
|
Sign up to set email alerts
|

Anti-aging effects of vitamin C on human pluripotent stem cell-derived cardiomyocytes

Abstract: Human pluripotent stem cells (hPSCs) have arisen as a source of cells for biomedical research due to their developmental potential. Stem cells possess the promise of providing clinicians with novel treatments for disease as well as allowing researchers to generate human-specific cellular metabolism models. Aging is a natural process of living organisms, yet aging in human heart cells is difficult to study due to the ethical considerations regarding human experimentation as well as a current lack of alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Since the first report by Takahashi et al [ 5 ], numerous groups have documented that AA promotes CM differentiation from both mouse and human ESCs and iPSCs [ 6 , 8 , 23 , 24 ]. AA is now considered indispensable for the routine production of hPSC-CMs using defined media [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first report by Takahashi et al [ 5 ], numerous groups have documented that AA promotes CM differentiation from both mouse and human ESCs and iPSCs [ 6 , 8 , 23 , 24 ]. AA is now considered indispensable for the routine production of hPSC-CMs using defined media [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transplanted mesenchymal stem cells (MSCs) are consistently exposed to tissue signals, immune cells and mediators that could influence their behavior. The mechanisms by which this environment influences potential therapeutic outcomes in MSC clinical applications remain poorly understood, however, over the past decade MSCs themselves have been shown to possess a broad spectrum of signaling capabilities, affecting both adaptive and innate immunity by the secretion of growth factors and chemokines to induce cell proliferation, angiogenesis, interactions with the immune system and mediation of anti-apoptotic events [ 1 , 2 ]. Based on these remarkable properties, the MSCs are considered to have therapeutic potential to treat broad spectrum of diverse human diseases, including cancer [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human embryonic stem cells (hESCs) are derived from the inner cell mass of human blastocyst stage embryos [11,12]. Human embryoid bodies (hEBs) are differentiated from hESCs [13,14] and can be used as a surrogate model [15,16] since they recapitulate many differentiation processes of early human embryonic development [17][18][19]. Previously, we have reported a feasible use for hEBs as an in vitro early human developmental model [20] and other studies showed that the progestational compound affected the differentiation of hESCs and hEBs [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%